Cerebral Blood Flow, Oxygen Delivery, and Pulsatility Responses to Oxygen Inhalation at High Altitude: Highlanders vs. Lowlanders - Xing, Chang-Yang; Serrador, Jorge M.; Knox, Allan; Ren, Li-Hua; Zhao, Ping; Wang, Hong; Liu, Jie (Frontiers in Physiology, 2019)
Objective: To determine whether the acute cerebral hemodynamic responses to oxygen inhalation are impacted by race or acclimation to high altitude. Methods: Three groups of young healthy males, i.e. Tibetans (highlanders, n = 15) with lifelong exposure to high altitude, and Han Chinese (lowlanders) with five-year (Han-5yr, n = 15) and three-day (Han-3d, n =16) exposures participated in the study at an altitude of 3658 m. The cerebral blood flow velocity (CBFV) was recorded for three minutes prior to and during pure oxygen inhalation (2 L/min) respectively, using a transcranial color-coded duplex sonography at the middle cerebral artery. The blood draw and simultaneous monitoring of blood pressure, heart rate, and finger arterial oxygen saturation (SaO2) were also performed. Results: Values are Mean ± SEM. The three groups had similar demographic characteristics and heart rate responses, with the group differences (P<0.05) found in hemoglobin concentration (16.9±0.9, 18.4±1.3, and 15.5±1.0 gm/dL), baseline blood pressures and heart rate as expected. Both the Tibetans and Han-5yr groups presented blunted blood pressure responses to O2-inhalation when compared to the Han-3d group; more interestingly, the Tibetans showed significantly reduced responses compared with Han-5yr and Han-3d in CBFV, cerebral oxygen delivery (COD), and pulsatility index (PI) as assessed by Δ%CBFV/ΔSaO2 (-1.50±0.25 vs. -2.24±0.25 and -2.23±0.27, P = 0.049 and 0.048), Δ%COD/ΔSaO2 (-0.52±0.27 vs.-1.33±0.26 and -1.38±0.28, P = 0.044 and 0.031), and Δ%PI (7±2 vs.16±3 and 16±3 %, P = 0.036 and 0.023) respectively. Conclusions: These findings provide evidence on the Tibetans trait of a distinct cerebral hemodynamic regulatory pattern to keep more stable cerebral blood flow, oxygen delivery, and pulsatility in response to oxygen inhalation as compared with Han Chinese, which is likely due to a genetic adaptation to altitude.